Fusion Rates of Intervertebral Polyetheretherketone and Titanium Cages without Bone Grafting in Posterior Interbody Lumbar Fusion Surgery for Degenerative Lumbar Instability - Wrangel, Christof von; Karakoyun, Ali; Buchholz, Kaye-Marie; Süss, Olaf; Kombos, Theodoros; Woitzik, Johannes; Vajkoczy, Peter; Czabanka, Marcus (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2017)
Background Posterior lumbar interbody fusion (PLIF) surgery is a commonly used procedure for degenerative lumbar instability. Locally harvested bone is usually inserted into intervertebral cages to increase fusion rate. The fusion rate without bone application remains unknown. Our aim was to analyze retrospectively the fusion rates of intervertebral polyetheretherketone (PEEK) and titanium cages in PLIF surgery that were implanted without bone grafting using three-dimensional computed tomography (CT) scanning.Material and Methods Forty patients (age 43–83 years) with mono- or bisegmental degenerative instability were included. PEEK cages were used in 28 segments (25 patients), and titanium cages were used in 17 segments (15 patients) undergoing PLIF surgery plus pedicle screws. The primary outcome parameter was radiologic fusion rate measured by CT at follow-up. Secondary parameters included rate of implant failure and adjacent segment disease.Results No difference in mean age between groups was identified (PEEK: 69 ± 10 years; titanium: 62 ± 13 years). Mean follow-up was 39 ± 13 months in PEEK and 24 ± 12 months in the titanium group. Radiologic fusion rate was 32% of operated segments in PEEK and 53% in the titanium group. Screw loosening/adjacent-level disease was observed in 8% and 8% in the PEEK group and in 0% and 7% in the titanium group, respectively.Conclusion Radiologic fusion rates of PEEK and titanium cages without bone grafting is low in PLIF surgery, and therefore bone grafting should be performed if possible. Rate of implant failure and adjacent-level disease remains low despite reduced osseous fusion in the operated segments.
Keywords: lumbar interbody fusion; PLIF; degenerative lumbar instability